2004
DOI: 10.1046/j.1540-8167.2004.03114.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Sinus Morphology in Patients With and Without Atrioventricular Nodal Reentrant Tachycardia by Intracardiac Echocardiography

Abstract: The CS os was significantly wider in patients with AVNRT than in those without. These findings may have important implications for arrhythmia pathogenesis in AVNRT as well as AFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…An increase in the length of the posterior extension of the AV node and slow pathway has been associated with an increase in the width of the coronary sinus os and might predispose to AVNRT possibly by increasing the length of the posterior extension of AV nodal slow pathway. However, this anatomic finding that has been reported to be noted more commonly in patients with AVNRT was not more common in women (10).…”
Section: Physiologic Basis For Clinical Clues To Svt Diagnosiscontrasting
confidence: 44%
“…An increase in the length of the posterior extension of the AV node and slow pathway has been associated with an increase in the width of the coronary sinus os and might predispose to AVNRT possibly by increasing the length of the posterior extension of AV nodal slow pathway. However, this anatomic finding that has been reported to be noted more commonly in patients with AVNRT was not more common in women (10).…”
Section: Physiologic Basis For Clinical Clues To Svt Diagnosiscontrasting
confidence: 44%
“…Lesions are usually created from the right side of the septum in the inferior or mid segment of the triangle of Koch [16], although the precise site of successful ablation is found over a wide midseptal or posteroseptal region [1, 57]. Some clinical investigators have suggested that the highly variable sizes and shapes of Koch’s triangle [810], and size and morphology of the coronary sinus (CS) ostium [11, 12], contribute to the variability in the location of successful ablation sites among patients. In particular, there are anatomic variations in the right posterior extension of the AV node, which act as SP during ongoing AVNRT [13], although neither their location relative to Koch’s triangle or the CS ostium nor the length of the SP (SP-L) have been evaluated clinically.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the precise anatomic location of SP is likely to optimize the safety of its ablation. Moreover, the methodological determinants of this individual variability in previous studies might be explained, at least in part, by the limited accuracy of fluoroscopy in identifying anatomic landmarks and the optimal ablation site [1, 57, 912, 14–16]. An electroanatomic mapping system (EAMS) might precisely track the tip of the mapping catheter and accurately measure the distance between two points in a three-dimensional space [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if both arrhythmias have a common area of the perinodal atrium in their tachycardia circuit, the width of the AFL circuit at the septal cavotricuspid isthmus should be larger than slow pathway location because of the wider, "windsock" appearance of the coronary sinus ostium in patients with AVNRT. 12 However, inducibility of AFL in patients with AVNRT may not predict spontaneous onset of AFL in the future.…”
Section: Resultsmentioning
confidence: 99%
“…12 If the same area is critical for AVNRT and AFL, AFL might be inducible in patients with AVNRT. Therefore, the purpose of this study was to evaluate the inducibility of AFL in patients with AVNRT and to determine if the inducibility of AFL is altered by RFCA of the slow pathway of the AVNRT circuit.…”
Section: Circulation Journal Vol70 September 2006mentioning
confidence: 99%